2004
DOI: 10.1117/12.559514
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical bioimaging and quantification of vasculature in disease models using corrosion casts and microcomputed tomography

Abstract: A wide range of disorders are associated with alterations of the central and peripheral vascular system. Modified vascular corrosion casting using a newly developed polymer, allows for the first time hierarchical assessment of 3D vessel data in animals down to the level of capillaries. Imaging of large volumes of vasculature at intermediate resolution (16 µm) was performed using a desktop micro-computed tomography system. Subsequently regions of interest were identified for additional high resolution imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Using vascular corrosion casts and scanning electron microscopy (SEM), 44 the 3D cerebrovascular architecture of 7-27 mo old APP23 and WT mice were characterized. [45][46][47][48][49] In WT mice vascular casts displayed a dense capillary network where arteries and veins were distinguishable by imprints of either elongated or rounded endothelial cells (ECs), respectively. 46 In contrast, APP23 mice displayed a multitude of vascular malformations including swelling, looping, twisting, and kinking, similar to vascular alterations present in the human AD brains.…”
Section: App23mentioning
confidence: 99%
See 2 more Smart Citations
“…Using vascular corrosion casts and scanning electron microscopy (SEM), 44 the 3D cerebrovascular architecture of 7-27 mo old APP23 and WT mice were characterized. [45][46][47][48][49] In WT mice vascular casts displayed a dense capillary network where arteries and veins were distinguishable by imprints of either elongated or rounded endothelial cells (ECs), respectively. 46 In contrast, APP23 mice displayed a multitude of vascular malformations including swelling, looping, twisting, and kinking, similar to vascular alterations present in the human AD brains.…”
Section: App23mentioning
confidence: 99%
“…47,[50][51][52] Functionally, flow patterns in WT mice were normal as measured by magnetic resonance angiography (MRA), but in APP23 mice 60 Minogue et al 63 Wang et al 62 Kelly et al 57 70 Giannoni et al 68 (continued) flow disturbances were observed in carotid arteries at 11 mo of age with significant flow voids in the major arteries of the Circle of Willis by 20 mo of age. 45,47,48 Moreover, vascular casts showed areas devoid of vessels that were sites of thioflavin S-positive Ab plaques.…”
Section: App23mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that compared AD models and WT also found negligible or no difference in capillary diameters. Heinzer et al compared a different mouse model (APP23) using MRA and found no difference between WT and AD mice [57]. The same group also compared the effects of "VEGF overexpression" model and WT using SRµCT and also found little difference [58].…”
Section: Aging and Alzheimer's Disease Have Little Effect On Capillarmentioning
confidence: 99%
“…VCCs were macerated, decalcified and stained with osmium tetroxide for better absorption contrast in the X-ray. 3D images of the full mouse brain vasculature were acquired with a desktop µCT system (µCT40, Scanco Medical, Bassersdorf, Switzerland), complemented by local SRµCT scanning (Materials Science Beamline, Swiss Light Source, PSI, Villigen, Switzerland) [8,10,11] for local regions of interest (ROI), using a nominal voxel size of 16 µm and 1.4 µm, respectively [8]. Tomographic image data was reconstructed using a filtered backprojection algorithm.…”
Section: Sample Preparation and Image Acquisitionmentioning
confidence: 99%